2023
DOI: 10.1186/s12909-023-04011-y
|View full text |Cite
|
Sign up to set email alerts
|

Well-being variations on students of health sciences related to their learning opportunities, resources, and daily activities in an online and on-crisis context: a survey-based study

Abstract: Background Universities’ training process intensely relies on face-to-face education. The COVID-19 pandemic interrupted it and forced them to reinvent their process online. But this crisis seems not to be the last we will face, and we take it as a lesson to prepare for future crises. These critical contexts are especially challenging because they imply changing teaching strategies, and students may not have the technology access or the living conditions to connect as they need. They also lived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…These events, marked by critical sociopolitical dynamics and needs for rapid adaptation, present a fertile ground to assess variations in subjective well-being, coping, and fields of spatial justice and habitability ( Astudillo Pizarro and Sandoval Díaz, 2019 ; Sandoval-Díaz et al, 2021 , 2022 , 2024 ). Moreover, employability circumstances such as job loss or absence, or significant changes in work conditions, as well as the loss of daily social activities and hospitalizations, are critical areas where the ECSS-20 could reveal significant impacts on mental and physical health ( Bahamondes-Rosado et al, 2023 ; Pérez-Villalobos et al, 2023 ). It is also advisable to explore how the ECSS-20 functions across different cultures and countries, as stress and its perception can vary considerably among different environments and populations ( Tasnim et al, 2024 ; Tonon et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…These events, marked by critical sociopolitical dynamics and needs for rapid adaptation, present a fertile ground to assess variations in subjective well-being, coping, and fields of spatial justice and habitability ( Astudillo Pizarro and Sandoval Díaz, 2019 ; Sandoval-Díaz et al, 2021 , 2022 , 2024 ). Moreover, employability circumstances such as job loss or absence, or significant changes in work conditions, as well as the loss of daily social activities and hospitalizations, are critical areas where the ECSS-20 could reveal significant impacts on mental and physical health ( Bahamondes-Rosado et al, 2023 ; Pérez-Villalobos et al, 2023 ). It is also advisable to explore how the ECSS-20 functions across different cultures and countries, as stress and its perception can vary considerably among different environments and populations ( Tasnim et al, 2024 ; Tonon et al, 2024 ).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, an online learning scenario that tries to emulate traditional learning focuses on expository strategies. Most students reported that their well-being deteriorated during the semester, but tutorials, workplace availability, and social support were protective factors (Pérez-Villalobos et al, 2023). There are many different types of learning methodologies, such as project-based learning, and students who are typically not accustomed to this structure are encouraged to take charge of their learning by talking with peers and other individuals about the advice they receive, the experiences they limit, and/or the opportunities they had to try something new (Konrad et al, 2021).…”
Section: Cost Of Livingmentioning
confidence: 99%
“…Institutions must have clear policies on online teaching-learning, ISSN: 2582-0974 [15] including expectations for teachers and students, assessment strategies, and technical support. Additionally, institutions must provide adequate resources and training for teachers to effectively teach online [23].…”
Section: (C) Institutional Policies and Supportmentioning
confidence: 99%